Microtopochemistry of pyrite nodules of siliceous siltstones from the Yubileinoe massive sulfide deposit (the Southеrn Urals): LA-IСP-MS data - Tseluyko, Alexander S.; Maslennikov, Valery V.; Artem’yev, Dmitry A. (Litosfera (Ekaterinburg. Online), 2018)
Object . The zonal pyrite nodules and metacrystals from siliceous siltstones of ore-bearing horizon of the Second ore body from the Yubileynoe massive sulfide deposit are studied. Materials and methods . We used 9 samples and 15 polished sections of siliceous siltstones with pyrite mineralization. Analysis of chemical composition minerals was determined by Tescan Vega 3 with an energy dispersive microprobe Oxford Instruments X-act (Institute of Mineralogy UB RAS, Miass). Quantitave LA-ICP-MS analysis of pyrite for major and trace elements was carried out using New Wave Research UP-213 laser microprobe coupled to an Agilent 7500 quadrupole ICP-MS housed (University of Tasmania, Australia). Results. Microtopochemistry was established that the diagenetic core of the nodule is characterized by trace elements of typical poikilites of quartz (Si) and alumosilicates (Si, Al, Mg, V, Cr, K, Na, Ca), rutile and titanite (Ti), inclusions of chalcopyrite (Cu), sphalerite (Zn), galena (Pb, Sb, Bi), tetrahedrite-tennantite (As, Sb), native gold, petzite, hessite (Au, Ag, Te), tellurobismuthite, altaite, and coloradoite (Te, Bi, Pb). Cobalt and Ni substitute for Fe2+. The rim of subhedral pyrite is depleted in most trace elements except for Ni and As. Subhedral pyrite became rich in chalcophile (Au, Ag, Sb, Bi, Cu, Zn, Hg) and lithophile (Ca, K, Na, Cr) elements at the final stage of growth of the nodule. Similar mineralogical and geochemical zonation is typical of the pyrite metacrystals, where a micro-grained core concentrates Pb, Bi and Te, and a rim of subhedral pyrite is depleted in most trace elements. Similarly to the nodules, the outer rim of pyrite metacrystals is enriched in most trace elements (Pb, Au, Ag, Sb, Cu, As, Mo, Cr, etc.). The nodules and metacrystals were formed from diagenetic micronodule of poikilite pyrite. Conclusions. It is suggested that mineralogical and geochemical differences in pyrite metacrystals and nodules are caused by the greater degree of development of rims of subhedral pyrite.